The physical and chemical characteristics of several accessions of sorghum cultivated on drylands in East Nusa Tenggara, Indonesia - Lince Mukkun; HERIANUS JUSTHIANUS D. LALEL; YASINTA LETEK KLEDEN (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mukkun L, Lalel HJD, Kleden YL. 2021. The physical and chemical characteristics of several accessions of sorghum cultivated on drylands in East Nusa Tenggara, Indonesia. Biodiversitas 22: 2520-2531. Many sorghums' accessions are widely cultivated in East Nusa Tenggara (ENT) Province, but no information is available on their physical and chemical properties. This study aimed to analyze the physical and chemical properties of several sorghum accessions cultivated in the dryland of ENT province. Seven sorghum accessions were obtained from farmers, namely Numbu, Kawali, Okin, red local, brown local, black local, and white local. Physical properties of the grain were carried out visually, including color, shape, and seed husks. Proximate content, total polyphenols, anthocyanins, and tannins were analyzed to determine each accession's chemical properties. Quantitative data were analyzed by ANOVA followed by Duncan Multiple Region Test (DMRT) at P?0.5. Meanwhile, qualitative data were tabulated and presented in tables and figures. The results showed that all sorghums have almost the same nutritional content as other staple food to develop into a food substitute for rice to support food security. Furthermore, local black sorghum contains high polyphenol compounds with high antioxidant activity, indicating that it has excellent potential to be developed into functional foods. The high anthocyanin content in black sorghum can also be developed into a safe and environmentally friendly food coloring